Invented spelling in English and pinyin in multilingual L1 and L2 Cantonese Chinese speaking children in Hong Kong - Zhou, Yanling; McBride, Catherine (Frontiers in Psychology, 2023)
This research examined the relations among Cantonese phonological awareness, invented spelling in Pinyin (in Mandarin), and invented English spelling in 29 first language (L1) and 34 s language (L2) Cantonese-speaking second and third graders in Hong Kong. The purpose of this study was to understand how phonological awareness skills across languages are associated in multilinguals. We compared the phonological skills in the two groups (i.e., L1 and L2 Chinese speaking children) for the three official languages (i.e., Cantonese, Mandarin, and English) spoken in Hong Kong. The two groups did not differ on Cantonese phonological awareness, Mandarin Pinyin invented spelling, or English invented spelling, but the L1 group performed significantly better than the L2 group on Mandarin Pinyin tone skills, with non-verbal intelligence and grade level statistically controlled. In both groups, all three of the phonological sensitivity measures were significantly correlated with one another. With group, grade, and nonverbal IQ statistically controlled, only Mandarin Pinyin invented spelling but not Cantonese phonological awareness uniquely explained English invented spelling performance. In contrast, Pinyin invented spelling was uniquely explained by both English invented spelling and Cantonese phonological awareness skills. Results highlight some phonological transfer effects across languages.